Mini-hidrociclones aplicados ao sistema de controle de sólidos na perfuração de poços de petróleo - Mognon, José Lucas (2015)
The drilling process is one of the most costly and polluting phases in oil production. In that stage, large amounts of drilling fluid are used for removing the drilled cuttings of the well. This fluid requires constant treatment, in the form of solid removal, so it can be properly reused for injection. This treatment is usually performed by a system that involves the use of hydrocyclones, sieves, rotational dryers and decanter centrifuges. The centrifuges, mainly responsible for fine solids recovery, has its application limited by the high installation and maintenance costs involved and platform space restrictions, and thus not being able to process the entire volume of circulating fluid in the drilling system. Thereby, the present work propose the use of mini hydrocyclones ( 30 c D mm  ) in support of decanter centrifuges, aiming a higher fine cuttings removal of drilling fluid. To this end, an operational and geometric parameters effects study were performed, followed by optimization, in order to obtain a geometry with high efficiency and low liquid ratio. This geometry, referred as optimal geometry, was then tested on the operation with different fluids (water+ carboxymethylcellulose) having rheological characteristics (pseudoplastic fluid) similar to the one commonly used in drilling process. Finally, the obtained results were implemented in a simulation of the optimum hydrocyclone, using for that, a granulometric size distribution from a centrifuge drilled cuttings sample and also analyzing the serial operation of the equipment. The results obtained for the optimal geometry showed high levels of total efficiency (81-89%) while maintaining reasonable values of underflow-to-throughput ratios. In sequence, empirical expressions for the pseudoplastic fluid operation were obtained for total efficiency, underflow-to-throughput ratio, cut diameter and flowrate, with coefficients of determination above 0.986. Finally, simulation results of serial operation showed that the tested hydrocyclones may promote a reduction of up to 24% on the fluid solid content, while also allowing high flexibility during the different phases of drilling.